Characteristics of Children With Persistent Pain and Their Parents in a Tertiary Interdisciplinary Pain Clinic - Ulla Caverius; Sophia Åkerblom; Jan Lexell; Marcelo Rivano Fischer (Paediatric & Neonatal Pain, 2025)
ABSTRACT Persistent Pain (PP) in children often has a high impact on their functioning. Knowledge about how to meet the needs is insufficient, especially regarding younger children, children with comorbid psychiatric health conditions, and within different national contexts. A specialized pediatric pain clinic for PP in Sweden offers assessment and interdisciplinary pain rehabilitation (IPR) and collects data on referred children and their parents in a registry. The aims of this study are to (i) describe clinically relevant aspects of children and parents at the first team assessment, (ii) investigate associations between symptoms of psychiatric comorbidity and functioning, (iii) investigate associations between symptoms of ADHD or symptoms of ASD and functioning, and (iv) describe the recommendations after the first team assessment and their rationale. A retrospective cohort study with a descriptive and exploratory design focusing on the characteristics of children (n = 510) and their parents at their first visit for specialized assessment at a tertiary pediatric pain clinic in Sweden between 2013 and 2021. Impairments and complexity appeared to increase with age, with high impact on daily and emotional functioning, especially in relation to symptoms of psychiatric comorbidity and ADHD or ASD. A majority of children and parents were uncertain about the cause of the pain. Only half of the children were recommended IPR, and numerous problems in functioning were found, not only related to pain. In agreement with previous studies describing characteristics of children with PP, there were more girls than boys and older than younger children at the first assessment. Both children and parents report several significant problems in physical, psychological, and social functioning, indicating a need for increased knowledge of PP and care in all kinds of pediatric health care and community settings. Tailored treatment interventions are recommended to improve functioning, including pain education, parental aspects, and addressing psychiatric comorbidities, with a special focus on ADHD or ASD symptoms. More thorough information to referring physicians about evaluations needed before referring to tertiary pain clinics could potentially help set the right expectations for further care and reduce the risk of diagnostic uncertainty.